Research progress of amorphous micro-nano structured materials - Liu, Gui; Huang, He (Frontiers in Materials, 2025)
Nanotechnology, centered on nanomaterials, represents a cutting-edge research domain. This review focuses on amorphous micro-nano materials (AMNMs), presenting their classification, structural features, basic properties, and synthesis methods. It details the research progress of AMNMs, including their structural characteristics, single-scale and multiscale composite structures, and construction processes. AMNMs exhibit significant potential in various applications, such as lightweight and high-strength materials, electronics and energy storage, medicine, and aerospace. However, challenges such as controllable synthesis and assembly into macroscopic materials remain. Future research should concentrate on developing new theoretical frameworks and synthesis methods to facilitate the practical application of AMNMs, deepening our understanding and driving their widespread use across multiple industries.